Analysis of student errors based on Polya’s steps in three-dimensional geometry - Nur'aini Muhassanah; Ana Setiani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
Students often experience difficulties in learning mathematics, particularly in solving word problems. Consequently, students make many errors when answering story questions in mathematics. The aim of this research is to describe students' mistakes according to Polya's theory in solving story problems on three-dimensional geometry materials. Student mistakes identified in Polya's theory include: understanding the problem, planning a solution, implementing the solution plan, and re-examining the obtained solution. The research method used is descriptive qualitative. The technique used is an interactive data analysis model from Miles & Huberman, which consists of four steps in analysis activities: data collection, data reduction, data presentation, and conclusion synthesis. The subjects of this research were 20 students from the Elementary School Teacher Education Study Program. The instruments used in this research are tests in the form of problem-solving questions and non-test instruments, including interviews. The results of the research indicate that many students made errors during the re-examination stage, primarily due to a lack of thoroughness in recording the conclusions from their calculations. For this reason, it is necessary to develop learning methods or models that improve the ability to understand concepts, use a variety of problem-solving strategies, and develop thinking process skills that can help reduce errors in solving mathematical problems.